The Modernization of Poland Defense Forces to Respond Russia Military Presence in Kaliningrad Oblast (2014-2017) - Anak Agung Banyu Perwita; Widya Dwi Rachmawati (Global Strategis, 2018)
The geopolitical security condition of Eastern Europe has undergone a drastic shift from Communist to Democratic ideology. After the collapse of the Soviet Union, Poland immediately joined the Western alliance, which led to the massive structural changes of the country. The shift has had an enormous impact on Russia where it has made various confrontations to regain its influence in the region. Russia continues to increase tensions by increasing the military capabilities of Kaliningrad Oblast, which is directly bordered by Poland. In response, the Polish government made efforts to modernize its military as part of the Defense White Book 2013 to improve its military capabilities in response to Russian military presence in Kaliningrad Oblast. The role of the global players (EU, NATO, and the USA) is key important to the security stability of the region. Poland on its four pillars specifically calls the alliance with the USA and becomes a member of NATO as an important factor in the formulation of its defense policy, in which Poland could increase the capabilities of its Armed Forces.